2022
DOI: 10.1007/s11030-022-10459-9
|View full text |Cite
|
Sign up to set email alerts
|

Amentoflavone derivatives significantly act towards the main protease (3CLPRO/MPRO) of SARS-CoV-2: in silico admet profiling, molecular docking, molecular dynamics simulation, network pharmacology

Abstract: SARS-CoV-2 is the foremost culprit of the novel coronavirus disease 2019 (nCoV-19 and/or simply COVID-19) and poses a threat to the continued life of humans on the planet and create pandemic issue globally. The 3-chymotrypsin-like protease (M PRO or 3CL PRO ) is the crucial protease enzyme of SARS-CoV-2, which directly involves the processing and release of translated non-structural proteins (nsps), and therefore involves the development of virus pathogenesis along… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 70 publications
1
25
0
Order By: Relevance
“…97 For example, Zhu and Xie found that procyanidin b2 forms hydrogen bonding interactions with GLY 143 and GLU 166, 97 and Dey et al found that bilobetin forms hydrogen bonding interactions with GLU 166 and HIS 163. 100 We observed these same interactions among others.…”
Section: Identification Of Lead Phytochemicals and Lead Clusterssupporting
confidence: 81%
“…97 For example, Zhu and Xie found that procyanidin b2 forms hydrogen bonding interactions with GLY 143 and GLU 166, 97 and Dey et al found that bilobetin forms hydrogen bonding interactions with GLU 166 and HIS 163. 100 We observed these same interactions among others.…”
Section: Identification Of Lead Phytochemicals and Lead Clusterssupporting
confidence: 81%
“…Through high-throughput screening, drug repurposing, and in silico prediction, many studies have been conducted to identify potential candidates for inhibiting SARS-CoV-2 infection [11] , [12] , [13] , [14] , [15] , [16] . Despite of the potential effects on viral replication and translation, many of these candidates still lack in vitro and in vivo experiments to validate their functions, and the requirement of the long period of clinical trials for human usage [13] , [17] , [18] . Currently, the approved antiviral drugs focus on blocking viral replication by targeting viral protease or RNA-dependent-RNA polymerase (RdRp), such as Paxlovid and Molnupiravir [19] , [20] , [21] , [22] , [23] , [24] , [25] .…”
Section: Introductionmentioning
confidence: 99%
“…Quercetin has also been discovered to have antiviral properties. Quercetin was found to be effective against human T-lymphotropic virus-induced budding in MT2 cells ( Coelho-dos-Reis et al, 2011 , Dey et al, 2022 ). Quercetin showed activity against dengue virus type-2 ( Mir et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%